Secondary liver cancer, metastasectomy multiple, jaundice due to pedicular neoplastic nodes, hepatic jejunostomy calibrated with tube transhepatic in line. Forty month survival - Praderi, Raúl C; Torterolo, Edgardo; Ottati, Alfio; Tiscornia, Eduardo (Cirugía del Uruguay, 1998)
A 64 year old fema/e underwent two-step surgery for cancer of the sigmoid. Thirty months /ater she developed tour metastasis in different hepatic lobes which were total/y resected. 19 months later she presented obstructive jaundice due to pedícle neoplastic nodes which did not exist in the initial surgery. Decompression was carried out by means of a transhepatic tube at right and she was reoperated undergoing hepaticojejunostomy by means of a transfixiant transhepatic tube. She was treated with 5-fluoracy/ and severa/ drainage replacements were performed. She died 21 months later. She survived metastasis for 40 months and six years overa//. The authors point out the curious sequence of hepatic metastasis at first and pedicle metastasis later which were treated in that order. Literature ana/ysis reveals few references to this situation and no similar cases.